A Study on the Biodiversity of Pigmented Andean Potatoes: Nutritional Profile and Phenolic Composition - Bellumori, Maria (2020)
The characterization of six varieties of native Andean potatoes with a wide biodiversity in tuber shape, flesh, and skin color was performed, through the determination of their proximate composition, mineral content, and phenolic profile. Minerals concentration revealed significant genotypic variation. Potassium was the most abundant element in all varieties, ranging from 7272.9 to 13,059.9 µg/g and from 12,418 to 17,388.6 µg/g dried weight for the flesh and skin samples, respectively. Iron content was relevant, ranging from 20.5 to 39.9 µg/g and from 112.2 to 288.8 µg/g dried weight in flesh and skin samples, respectively. Phenolic compounds were consistently higher in the skin than in the flesh. The total content varied greatly from 19.5 to 2015.3 µg/g and from 1592.3 to 14807.3 µg/g dried weight for flesh and skin tissues, respectively. 5-caffeoylquinic acid was 74% of the total phenolic acids. Different pattern of anthocyanins was found, depending on the color of the variety; the red genotypes contained predominantly pelargonidin derivatives, while the purple samples had petunidin as a major anthocyanidin. This study increases the knowledge of the composition of the local Andean varieties (which are only scarcely studied so far), helping to enhance these genotypes and the conservation of biodiversity.